2014
DOI: 10.1007/s12031-014-0260-4
|View full text |Cite
|
Sign up to set email alerts
|

PACAP Enhances Barrier Properties of Cerebral Microvessels

Abstract: Cerebral microvascular endothelial cells-coming in contact with pericytes and astrocytes-constitute the structural basis of the blood-brain barrier (BBB). The continuous belt of interendothelial tight junctions (TJs) and the presence of specific transport systems, enzymes, and receptors in the brain endothelium regulate the molecular and cellular traffic into the central nervous system. Pituitary adenylate cyclase-activating polypeptide (PACAP) is a neuropeptide having several cellular protective effects. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
(31 reference statements)
2
9
0
Order By: Relevance
“…Altogether, these fi ndings show that both peptides counteract high glucose + IL-1β-induced damage in ARPE19 cells, suggesting that they might be relevant to the maintenance of outer blood-retinal barrier function in edema accompanying diabetic retinopathy [ 55 ]. These results are in accordance with our earlier observations in an in vitro blood-brain barrier (BBB) model [ 56 ]. We found that PACAP treatment improved the barrier properties of the brain endothelium.…”
Section: In Vitro Protective Effects In the Retinal Pigment Epitheliasupporting
confidence: 92%
See 1 more Smart Citation
“…Altogether, these fi ndings show that both peptides counteract high glucose + IL-1β-induced damage in ARPE19 cells, suggesting that they might be relevant to the maintenance of outer blood-retinal barrier function in edema accompanying diabetic retinopathy [ 55 ]. These results are in accordance with our earlier observations in an in vitro blood-brain barrier (BBB) model [ 56 ]. We found that PACAP treatment improved the barrier properties of the brain endothelium.…”
Section: In Vitro Protective Effects In the Retinal Pigment Epitheliasupporting
confidence: 92%
“…PACAP induced an increase in the transendothelial electrical resistance, which is the most important marker of the tightness of the tight junctions. Moreover, PACAP had a protective role against glucose deprivation-and oxidative stressinduced junctional damage in microvascular brain endothelial cells [ 56 ].…”
Section: In Vitro Protective Effects In the Retinal Pigment Epitheliamentioning
confidence: 96%
“…Therefore, given its contribution to age-related brain vulnerabilities, large efforts are underway to restore BBB function. In this regard, the pituitary adenylate cyclaseactivating polypeptide was found to strikingly improve transendothelial electrical resistance and BBB tightness, as well as to protect against glucose deprivation and oxidative stress-induced junctional damage [137].…”
Section: Impairment Of Blood-brain Barrier Properties In Agingmentioning
confidence: 99%
“…Besides its general cell protective, prosurvival, and anti‐inflammatory effects, PACAP might possess protective effects on TJs of endothelial and epithelial cells . PACAP stabilizes the junctional proteins in the membrane of brain endothelial cells both in control and in pathological conditions (e.g., glucose deprivation and oxidative stress) . Moreover, PACAP was shown to have a protective effect on the barrier properties of the cells of the o‐BRB in the presence of factors accounting for diabetic macular edema (i.e., high glucose and interleukin‐1β) .…”
Section: Introductionmentioning
confidence: 99%